A new approach for the measurement of the volume expansion of a CO2 + n-dodecane mixture in a fused silica capillary cell by Raman spectroscopy. (1st September 2017) - Wang, Junliang; Zhou, Shuyan; Bei, Ke; Chou, I-Ming; Lin, Chunmian; Pan, Zhiyan
Highlights: Determination of the volume expansion of CO2 + n -dodecane with FSCC and Raman spectra. Water seal between n -dodecane and gas phase to prevent n -dodecane from evaporating. A quadratic relationship between Raman peak intensity ratio and volume expansion. Abstract: This work developed a new method for measuring the volume expansion of a CO2 + n -dodecane mixture, using a fused silica capillary cell (FSCC), combined with a heating-cooling stage and a confocal Raman spectrometer. The cell was constructed on the micron scale to reduce the temperature gradient and reagent consumption. The results confirmed the feasibility of this method that using Raman spectra to verify phase equilibrium, a digital camera to record images of the CO2 + n -dodecane mixture and a micrometer to measure the volume, a section of water (water seal) between n -dodecane and gas phase to prevent n -dodecane from evaporating. It was shown that the volume expansion factor of the mixture increased with pressure going from 1.0 to 10.0 MPa, but decreased as the temperature was raised from 30 to 80 °C. In addition, a positive quadratic relationship ( R 2 > 0.99) was obtained between Raman peak intensity ratio and volume expansion factor, such that more volume expansion factors could be obtained according to the equations with measured Raman peak intensity ratio data. This experiment widens the ranges of temperature and pressure in the measurements of the volume expansion, and provides more volume expansion data for CO2 -enhanced oil recovery.